Pelaksanaan amalan kepemimpinan kolaboratif dalam kalangan pemimpin instruksional bagi memperkasakan pendidikan matematik sekolah rendah / Wan Noor Adzmin Mohd Sabri - Wan Noor Adzmin, Mohd Sabri (2017)
This qualitative research study discusses the collaborative leadership practices of instructional leaders, found to enhance primary schools mathematics. This case study was conducted using three data collectioned techniques namely interviews, observations and document analysis. Purposive sampling was used to select ten participants from three schools. These include the school head, senior assistants, head of the mathematics department and the mathematics teachers. The findings indicate that School C conceptualized the practices of the collaborative leadership through team teaching and relationship management, while Schools A and B showed informal collaborative leadership practices. Findings also showed that all the three schools implement collaborative leadership practices to enhance mathematics in aspects of leader plus, pactice aspect, building and relationship management. Although there are some similarities in the elements such as organisation tools, routine, relationship management and relationship building, the implication of this research according to Spillane (2006) and Rubin (2009) models showed that collaborative leadership has not been fully implemented in Malaysian schools.